Russkij jazyk v perelomnoe vremja: 1985 - 1995 g.g - Spraul, Hildegard; Peters, Wolfgang; Spraul, Hildegard; Peters, Wolfgang (Bern Peter Lang International Academic Publishing Group, 1996)
Slavic languages
German
Keywords: Language teaching & learning (other than ELT); Slavic languages